Thermometers for Non-Contact Temperature Measurement (Eurasian Research Bulletin, 2022)
The article is devoted to the study and analysis of modern non-contact infrared thermometers. The principles of work and general trends in the development of non-contact thermometers are analyzed. Criteria for the selection of non-contact thermometers are given and their advantages are listed